2002
DOI: 10.1074/jbc.m208737200
|View full text |Cite
|
Sign up to set email alerts
|

A Conditional Mutation Affecting Localization of the Menkes Disease Copper ATPase

Abstract: Copper is an essential co-factor for several key metabolic processes. This requirement in humans is underscored by Menkes disease, an X-linked copper deficiency disorder caused by mutations in the copper transporting P-type ATPase, MNK. MNK is located in the transGolgi network where it transports copper to secreted cuproenzymes. Increases in copper concentration stimulate the trafficking of MNK to the plasma membrane where it effluxes copper. In this study, a Menkes disease mutation, G1019D, located in the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…First, mutation-induced mislocalization away from the early endosomal membrane would remove SIMPLE protein from its site of action, thereby contributing to CMT pathogenesis by a lossof-function mechanism (Kim et al, 2002;Lupo et al, 2009;Roberts et al, 2010). Although the cellular function of SIMPLE is unknown, it has been proposed that SIMPLE might participate in protein sorting at the early endosome (Shirk et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…First, mutation-induced mislocalization away from the early endosomal membrane would remove SIMPLE protein from its site of action, thereby contributing to CMT pathogenesis by a lossof-function mechanism (Kim et al, 2002;Lupo et al, 2009;Roberts et al, 2010). Although the cellular function of SIMPLE is unknown, it has been proposed that SIMPLE might participate in protein sorting at the early endosome (Shirk et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…One indication that the folding defect of the mutant protein may be reverted by the use of chemical chaperones is the increase of the polypeptide folding efficiency upon expression at lower temperature (72,195). Another is the increase in the export of the select functional polypeptide from the ER upon inhibition of ERAD (392) as the folding and degradation processes are for many proteins in kinetic competition (268a).…”
Section: B Pharmacological and Chemical Chaperones To Rescue Structumentioning
confidence: 99%
“…In any case, studies with chemical chaperones offered an important proof of principle and paved the way for characterization of several, substrate-specific pharmacological chaperones that proved efficient in cultured cells or that have already been used in animal and/or clinical trials (22,58,232,271). Here are a few selected examples: V2 receptor antagonists rescued mutant vasopressin receptor from proteasomal degradation (272); gonadotropin-releasing hormone (GnRH) peptidomimetics rescued secretion of several GnRH mutants (177); the cromophore retinal rescued maturation of mutant opsin (285); specific inhibitors facilitated maturation and transport of mutant voltage-gated potassium channels (93), beta-glucocerebrosidase (334), and ␣-D-galactosidase (90); copper supplementation alleviated maturation defects of the mutant copper transporting ATPase (195); and 4-phenylbutyrate corrected folding defects of several cystic fibrosis channel mutations (434).…”
Section: B Pharmacological and Chemical Chaperones To Rescue Structumentioning
confidence: 99%
“…30,48,59,60). Many mutations causing Menkes and Wilson diseases have been identified and studies conducted to understand a specific mutation's effect on protein expression, stability, or function (10,18,19,40,61). In addition, studies of the cellular basis of the normal proteins' dual functions have revealed that both ATP7A and ATP7B proteins change their intracellular locations in response to changes in copper levels (30).…”
mentioning
confidence: 99%